The Effect Of Christian Religious Education (PAK) On Special Needs (ABK) In The Inclusive School Of Sukolilo Areas In Understanding The Word Of God - Lilis Setyarini; Kasiatin Widianto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
Christian education is important in the family and school environment. There is no exception for schools that accept students / students with special needs. However, it should be noted that the teaching and learning process of Christian education often has problems, especially in public schools. Problems that arise are mainly caused by unpleasant learning conditions, which are caused by not having a permanent learning place. Always moving around, and the place is sometimes not suitable for students to study, such as in a warehouse, in rooms that have never been used, near bathrooms that are not insulated, in the teacher's room, in the library, etc. thus experiencing obstacles in the teaching and learning process. This of course does not meet the maximum yield target. There are also internal barriers, namely from the students themselves. one of them is disabled children, both physically and mentally. The learning process of disabled children cannot run smoothly due to their disability. Based on the hypothesis test there is a relationship and influence of